Capital Structure, CEO Duality, and Their Role in Enhancing Financial Sustainability: Insights from Vietnamese Firms - Nguyen, Huong Thi Thanh; Ting, Irene Wei Kiong; Le, Hanh Thi My (Asian Academy of Management Journal of Accounting and Finance, 2025)
This study investigates the influence of capital structure and CEO duality on firm financial sustainability, using a panel dataset of publicly listed companies in Vietnam from 2018 to 2022. Two dimensions of sustainability are examined: financial sustainability and operational self-sufficiency, capturing both financial and operational performance. Employing the Generalised Least Squares method, the analysis reveals that capital structure metrics namely debt to total assets and debt to equity ratios significantly affect firm sustainability outcomes, with CEO duality serving as a moderating variable. The findings indicate that a higher debt to total assets ratio adversely impacts both financial sustainability and operational self-sufficiency. In contrast, a higher debt to equity ratiois positively associated with financial sustainability and CEO duality moderates the influence between capital structure and financial sustainability. These results highlight the role of optimal capital structuring and strategic leadership in sustaining firm performance. The study contributes to the literature on corporate governance in emerging markets and provides practical implications for policymakers, management teams, and investors, emphasising the importance of leadership configuration and financing strategies in promoting long-term sustainability.